The experiences and meanings of recovery for Swazi women living with "schizophrenia". Issue 5 (27th May 2019) - Nxumalo Ngubane, Siphiwe; McAndrew, Sue; Collier, Elizabeth
Accessible summary: What is known on the subject?: While there is no single definition of the concept of recovery for people with mental illness, hope has been recognized as a guiding principle; the belief that it is possible for a person to regain a meaningful life, despite serious mental illness. Little is known about the recovery process of women diagnosed with schizophrenia per se, with only six studies offering the woman's voice identified and these all having taken place in developed countries. No studies on this topic have been carried out in Sub‐Saharan Africa, including Swaziland. What this paper adds to existing knowledge?: This study provides unique insight into what is important to Swazi women, diagnosed with schizophrenia, in their process of their recovery. Because of current trends in migration, the findings of this study may provide mental health professionals with a better understand of the needs of those from this particular Sub‐Saharan country. The study discusses a range of issues affecting women including being labelled as mentally ill, stigma and discrimination, the importance of the sociocultural context of illness and positive attributes which promote women's recovery. What are the implications for practice?: This study provides mental health practitioners with insights and understanding of the lives of women from a Sub‐Saharan developing country. This will be helpful for better understanding of the context of mental illness both for practitioners supporting the development of services in such countries and for those working in Western countries with migrant populations. Abstract: Introduction: Globally, twenty‐four million people live with schizophrenia, 90% living in developing countries. While most Western cultures recognize service user expertise within the recovery process, this is not evident in developing countries. In particular, Swazi women diagnosed with schizophrenia experience stigma from family, community and care providers, thus compromising their recovery process. Aim: This study aimed to explore the experiences and meanings of recovery for Swazi women living with schizophrenia. Methodology: Interpretive phenomenological analysis was used. Fifteen women were recruited from Swaziland National Psychiatric Hospital out‐patients' department, and face‐to‐face interviews were conducted. Findings: Four super‐ordinate themes were identified: (a) The emotionality of "illness of the brain"; (b) Pain! Living with the illness and with others; (c) She is mad just ignore her; and (d) Being better. Discussion: Discussion focuses on the findings of this study and a number of positive and negative implications emanating from them: labelling, stigma and the roles of family, culture and religious beliefs on the process of recovery. Implications for practice: This study provides practitioners with insight into the importance of the sociocultural context of the lives of women diagnosed with schizophrenia and how, in understanding this, mental health care could be improved.